Updated list of Tersilochinae (Hymenoptera, Ichneumonidae) of Italy - Filippo Di Giovanni; Davide Dal Pos; Andrey I. Khalaim (Biodiversity Data Journal)
The subfamily Tersilochinae is a small taxon that accounts for about 60 species in Italy. However, the current checklist of the group is incomplete and listed records are often imprecise.An updated checklist of the Italian Tersilochinae is provided. Three species are new additions to the Italian fauna, while three others are first records for southern Italy. Additionally, Aneuclis pusilla Masi, 1933 is reported as a junior synonym of Aneuclis melanaria (Holmgren, 1860) syn. nov. This update raises the total number of Tersilochinae species in Italy to 77.